Additional Losses in Ultra-Wide Band Reflector Systems - Kara, Hazel; Tokan, Nurhan Turker (APPLIED COMPUTATIONAL ELECTROMAGNETICS SOC, 2016)
The increasing demand of ultra-wide band (UWB) antennas in reflector systems, especially for radioastronomy, necessitates the analysis of reflector losses for directive UWB feeds. UWB technology has significant advantages; however its usage in reflector systems brings some extra losses to be considered. 'Ideally, all areas of the reflector should be illuminated with equal energy from the feed antenna at all frequencies of the band. However, this is not possible for a wide band system. Different phase center locations and 10 dB beamwidth values at different frequencies within the band result in spillover, amplitude taper and phase losses in a reflector system. These losses should be analyzed in detail for the effectively working of the system. The purpose of this work is to discuss the additional losses that occur in a UWB reflector system and demonstrate these losses with a given example. A directive Vivaldi antenna is used as the feed antenna of the UWB reflector and the effect of the losses on the directivity is shown.
Keywords: Amplitude taper loss; cross-polarization loss; phase error loss; reflector; spillover loss; Vivaldi; UWB; ANTENNAS; Engineering; Telecommunications